SERUM MYOSTATIN IS ASSOCIATED WITH PULSE WAVE VELOCITY RATIO IN HEALTHY ADOLESCENTS. THE MACISTE STUDY. (June 2022) - Pucci, Giacomo; D'Abbondanza, Marco; Curcio, Rosa; Alcidi, Riccardo; Campanella, Tommaso; Chiatti, Lorenzo; Veca, Vito; Sanesi, Leandro; Anastasio, Fabio; Nunziangeli, Luisa; Ministrini, Stefano; Vaudo, Gaetano
Abstract : Objective: Serum myostatin (sMSTN) is a proteic compound that regulates muscle growth and production of extracellular matrix. sMSTN also exerts profibrotic and antihypertrophic effects on smooth muscle cells and fibroblasts. Aortic-brachial pulse wave velocity ratio (PWVr) is a pressure-independent measure of arterial stiffness gradient between the aorta and peripheral muscular arteries, known to reflect early arterial ageing and to be associated with cardiovascular (CV) risk. We explored the association between sMSTN and arterial stiffness gradient, measured through the PWVr, in a cohort of healthy adolescents. Design and method: 128 healthy subjects (mean age 17 ± 2 years, 59% men) were randomly recruited among participants of the Metabolic And Cardiovascular Investigation at School, TErni (MACISTE) study, a cross-sectional survey conducted at the "Renato Donatelli" High School in Terni, Italy. sMSTN was measured through enzyme-linked immunosorbent assay. PWV was measured by applanation tonometry (SphygmoCor) along the carotid-femoral (cf-PWV, aortic) and the carotid-radial (cr-PWV, brachial) pathways and expressed as the ratio between cf-PWV and cr-PWV. Blood pressure (BP) was recorded at the same time of PWV measurement and expressed as systolic/diastolic BP percentiles (z-score) based on age, sex and height. Results: Mean BP was 126 ± 12/68 ± 8 mmHg (z-score 1.2 ± 0.9/0.3 ± 0.7). Mean Cf-PWV was 5.1 ± 0.9 m/s, cr-PWV was 6.9 ± 0.9 m/s. PWVr was 0.75 ± 0.12. PWVr increased linearly at increasing quartiles of sMSTN (0.71 ± 0.09, 0.74 ± 0.13, 0.75 ± 0.14, 0.78 ± 0.12, p for trend = 0.03, Figure 1). Subjects with PWVr above average had higher BMI (21.7 ± 2.6 Kg/m2 vs 20.8 ± 2.3 Kg/m2, p = 0.04) and SBP (1.39 ± 0.97 vs 0.97 ± 0.91, p = 0.01), whereas they did not differ in terms of age, sex, heart rate, measures of adiposity, and other CV risk factors. In a multivariate linear model, PWVr was independently predicted by SBP and sMSTN, both if expressed as continuous variable (beta = 0.21, p = 0.018) or in quartiles (beta = 0.26, p = 0.011). Conclusions: In a cohort of healthy Italian adolescents, sMSTN was positively and independently associated to increased PWVr, a measure of arterial stiffness gradient. Our preliminary results raise the hypothesis that sMSTN might differentially interfere with structural and functional components of the arterial wall, and ultimately might contribute to the accelerated arterial ageing in adolescents.